New aqueous nanolime formulations for fully compatible consolidation treatments of historical mortars for hypogeum environment. (21st November 2022) - Daniele, V.; Rosatelli, G.; Macera, L.; Taglieri, G.
Highlights: New nanolime-based treatments for the conservation of historical mortars in hypogea. Innovative aqueous nanolime formulations, pure or properly chemically tailored. Nanolime particles produced by a single-step, time/energy-saving and scalable route. The treatment effectiveness is evaluated by means of standard procedures. Abstract: The religious buildings characterizing by hypogea environments need of proper restoration interventions by using compatible materials. At now, organic and inorganic products proved to be inappropriate for this scope, in relation to the lack of chemical compatibility with the original substrate, to poor penetration depth and to the irreversibility of the treatments. Aim of this paper, is to present an innovative approach to safeguard the hypogea environment, by using new aqueous nanolime formulations, properly chemically tailored, for eco-friendly and green consolidation treatments. Phase composition, stability, and reactivity of the nanolime formulations were investigated, and chemical, petrographic and mechanical analyses of the mortar samples from the hypogeum were carried out. The treatments effectiveness was evaluated in terms of aesthetical features, superficial cohesion and mechanical improvement. The aqueous nanolime suspensions, pure and tailored, applied by airbrush, increase the superficial cohesion up to 95 % and improve the mechanical resistance of the surface and up to at least 1 cm in depth, without causing appreciable surface chromatic alterations.